Pollution in Keban dam lake: Trace metals from classical activated sludge system - Cuci, Y; Hasar, H; Yaman, M; Ipek, U (Springer-Verlag, 2001)
[Abstract Not Available]
Keywords: Atomic-Absorption Spectrometry; Carbon Enrichment; Vegetables; Lead; Preconcentration; Vanadium; Matrices; Cadmium